Multilayer Structure Technique for Improving Determination of Electromagnetic Properties of Radar Absorbers Based on Two-Layer Method and Flanged Rectangular Waveguide Probe - Abdulkadhim Ameen Hassan; Janan Hammed Saadie (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This paper presents further development of utilization of  two-layer method to perform nondestructive electromagnetic properties determination of planar radar absorbers using flanged  open-ended rectangular waveguide probe. A multilayer  structure  of three layers was proposed to improve the measured results of these parameters obtained using two-layer method. These layers were arranged  such  that the test  material is sandwiched between two known low  loss materials to provide the  needed  two independent reflection coefficients necessary to extract them  at different conditions of  testing. The proposed  structure was aimed  to decrease the effect  of direct backing of test material by metal plate, which influences measurement accuracy if  two-layer  method  is used.  The structure permits a suitable electric field interrogation  in test material and decreases the influences of both  radial and surface waves.  FDTD method  was adapted  for  modeling  the problem geometry  to calculate  the reflection coefficients  since a probe with finite flange size is used. Measurements were carried out using the proposed technique to determine complex permittivity and complex permeability of several radar absorbers over X-band  applications of  microwaves. In comparison with both single-layer and two-layer methods results, the measured   results of  these parameters  agreed  well with the published data. by companies and literatures.